Can the Environmental Law perspectives help improve our comprehension of human rights within International Law? - Pinto-Bazurco Barandiarán, José Félix (2022)
Even though some legal systems acknowledge the right to a healthy environment as a fundamental right, this acknowledgment is not universal yet. In this article, we explore the relationship between the right to a healthy environment and human rights; its status and its approach to be recognized in the international human rights system. To that end, an analysis of the strategic actions presented before justice tribunals as a tool to achieve said recognition is included.